THE HEMODYNAMIC EFFECTS OF COMBINED SPINALEPIDURAL VERSUS SPINAL ANESTHESIA IN CESAREAN SECTION - Zerary, Mohanned Wajeeh Saeed; Mohammed, Van Nasih; Boujan, Amir Murad Khudadad (Journal of Sulaimani Medical College, 2022)
Background Hypotension and bradycardia are the main problems in parturients anesthetized with spinal anesthesia for cesarean section. It is a common cause of maternal and fetal morbidity and mortality; the combined spinalepidural anesthesia technique is a new way to solve the problem. Objectives The hemodynamic effects of combined spinal-epidural anesthesia will be compared to spinal anesthesia alone in cesarean section. Patients and Methods After the approval of the local ethical committee and taking patients’ consent, 100 parturients at Sulaimani Maternity Hospital scheduled for cesarean section were involved in the study. They were divided into two groups; group S (n_50) received (3ml) of bupivacaine in a single spinal shot technique. Group CSE (n_50) received (2 ml) of the same drug with the insertion of an epidural catheter to give additional doses later in a combined spinal-epidural technique. Blood pressure and pulse rate were measured regularly at 5 minutes intervals throughout the operation. After shifting the patient to the ward, they continued the measurement postoperatively for one hour with 15 minutes intervals. Results Hypotension was more common in group S in 42 cases versus 7 in the CSE group. It was significant (P=0.012). Also, bradycardia occurred in 15 cases in the S group while it was only in 6 cases in the CSE group which were significant (P = 0.008). Conclusion The maternal hemodynamic changes were less significant with the combined Spinal-Epidural technique compared to routine spinal anesthesia of cesarean section.
Keywords: Combined spinal-epidural; cesarean section; hypotension; bradycardia